Web-based laundry management system / Ang Cheng Siong - Ang , Cheng Siong (2002)
Nowadays, information technology has pervaded into almost every industry in the country. Business organization today are moving to computerized their current systems to ensure smoother operations in the daily running of the business. Web-based Laundry Management System is introduced as to give a new impulse for the organization to gain more competitive advantages. The Waterfall with Prototyping Model has been chose as the methodology of system development to develop the proposed system. Beside the waterfall with prototyping model, a survey have had carried out to gather more information. This system was used JSP as web programming language" MySQL as the database and Apache and Tomcat as the web server. This system consists of two section and several modules. The two sections are member section and administrator sections. The member section will enable the member to register to join as member and place the order. The administrator section enables the administrator to view the order, change order status and generate the report. Web-based Laundry Management system is an online ordering system for the laundry business, which is developed with the purpose to gain more competitive advantages and reduce the problems such as losing receipt and unclaimed clothed (storage spaces) that currently facing by using manual system.